2010
DOI: 10.1007/s00436-010-2096-3
|View full text |Cite
|
Sign up to set email alerts
|

Morphological alterations and growth inhibition of Leishmania (L.)amazonensis promastigotes exposed to zidovudine (AZT)

Abstract: Leishmania parasites cause a worldwide public health disease and its treatment is still based on pentavalent antimonials which present financial and toxicologic limitations. Some nucleosidic derivatives have demonstrated anti-leishmanial properties and this study aims to evaluate the in vitro morphologic alterations and growth inhibition of Leishmania (L.) amazonensis promastigotes exposed to zidovudine at several concentrations. The citotoxicity of zidovudine (AZT) to macrophages was determined by an MTT assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Moreover, we were able to confirm dTTP and AP 5 dT as potent inhibitors of Lm TK. We showed AZT and 5’-modified dUrd to be readily phosphorylated by LmT K and this compound was shown previously to inhibit Leishmania intracellular amastigote growth and to exhibit potential as an antiprotozoal agent [ 54 ]. However, the lack of major structural differences in the active site of Lm TK compared to the hTK1, further validated by the similarity in their kinetic parameters for dUrd, 5F-2’dU and AZT ( Table 2 ), might render the design of Lm TK-specific ligands challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we were able to confirm dTTP and AP 5 dT as potent inhibitors of Lm TK. We showed AZT and 5’-modified dUrd to be readily phosphorylated by LmT K and this compound was shown previously to inhibit Leishmania intracellular amastigote growth and to exhibit potential as an antiprotozoal agent [ 54 ]. However, the lack of major structural differences in the active site of Lm TK compared to the hTK1, further validated by the similarity in their kinetic parameters for dUrd, 5F-2’dU and AZT ( Table 2 ), might render the design of Lm TK-specific ligands challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported antiprotozoal activity of HAART in Leishmania (Araújo et al, 2011;Kumar et al, 2008;Santos et al, 2009;Savoia, Allice, Tovo, 2005;Valdivieso et al, 2010). AZT significantly decreased the number of Leishmania parasites due to its toxicity and caused morphometric alterations such as an increase in width of the body, cytoplasmic granulation and vacuolization (Araújo et al, 2011).…”
Section: Antiretroviral Drugs and Protozoa Agentsmentioning
confidence: 99%
“…AZT significantly decreased the number of Leishmania parasites due to its toxicity and caused morphometric alterations such as an increase in width of the body, cytoplasmic granulation and vacuolization (Araújo et al, 2011). PIs such as ritonavir, indinavir and saquinavir have reduced the number of Leishmania promastigotes in vitro (Savoia, Allice, Tovo, 2005).…”
Section: Antiretroviral Drugs and Protozoa Agentsmentioning
confidence: 99%
“…Although there are limited in vitro data suggesting that HIV-1 protease inhibitors and possibly some other antiretroviral drugs might directly exert inhibitory effects on Leishmania , there is insufficient evidence for their clinical use against VL, and standard ART regimens are currently recommended in VL–HIV coinfection ( 5 ). In low income countries, this is provided by standardized first- and second-line regimens in a public health approach ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%